CASE: Managing key account disruption in the logistics industry - Carolin Wernicke; Samy Saab; Michael Kleinaltenkamp (jbm - Journal of Business Market Management, 2014)
Carl Rogers needs to make up his mind on what to suggest to his boss. There have been major changes in the buying center of the key account customer he is responsible for. He now needs to decide how to continue the existing relationship and how to proceed with the potential new ones.
urn:nbn:de:0114-jbm-v7i3.1029
Keywords: 650; Key Account Management; Buying Center; Logistics Industry